PROGRAM PARENTING DAN MOTIVASI PENDIDIKAN PADA TEMU BULANAN ANAK YATIM BINAAN LEMBAGA DSNI AMANAH KOTA BATAM - Sarmini; Cevy Amelia; Rini Susanti (LPPM Universitas Ibnu Sina, 2022)
The success of Management in Social Institutions is one of the benchmarks for the trust of service users and donors. Zakat, infaq and alms institution DSNI Amanah is one of the Best Social Institutions in Batam City. This article describes the Education Program for the Monthly Gathering of Fostered Children and Orphans with Parenting and Motivation as the program, which is the DSNI Amanah Program which is the Best Social Institution for Batam City. The flagship programs of DSNI Amanah that are different from other similar Social Institution programs are the Main Programs, namely: Communities Become Independent Characters:1. C-MED (Center For Micro-Medium Entrepreneurship Development) namely community independence with empowerment, 2. C-EP (Center For Education Program) or Education Scholarship Program, 3. C-SS (Center For Social Services) or Social Programs, 4 PPA (Argo Islamic Boarding School) which is a Character Islamic Boarding School Program, 5. PDP (Productive Village Assistance) Program for placing Da'i in Remote Hinterland. Achievement DSNI Institution is the first zakat institution in Indonesia to receive ISO 9001 certification. Implementation of Parenting and Motivation in this Monthly Meeting, on Sunday, February 27, 2022. With the aim of increasing insight and knowledge for DSNI fostered children and orphaned mothers. From the Parenting event, it is hoped that orphaned children and mothers, as well as poor people will know more about Parenting Patterns and Educational Patterns that Affect Children's Mindsets. As well as additional knowledge related to Online and Offline Learning that is being carried out in children's education